Effect of ship tilting and motion on amine absorber with structured‐packing for CO2 removal from natural gas. Issue 12 (1st August 2015) - Pham, Dung Anh; Lim, Young‐Il; Jee, Hyunwoo; Ahn, Euisub; Jung, Yongwon
Abstract : A gas‐liquid Eulerian porous media computational fluid dynamics (CFD) model was developed for an absorber with structured packing to remove CO2 from natural gas by mono‐ethanol‐amine (MEA). The three‐dimensional geometry of the amine absorber with Mellapak 500.X was constructed to investigate the effect of the tilting and motion experienced on ships and barges for offshore plants. The momentum equation included porous resistance, gas‐liquid momentum exchange, and liquid dispersion to replace structured‐packing by porous media. The mass equation involved mass transfer of CO2 gas into MEA solution, and one chemical reaction. Parameters of the CFD model were adjusted to fit experimental data measured in the CO2 ‐MEA system. As the tilting angle increased, the liquid holdup and effective interfacial area decreased and CO2 removal efficiency was lowered. The uniformity of liquid holdup deteriorated by 10% for a 3° static tilting, and a rolling motion with 4.5° amplitude and 12 s period, respectively. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4412–4425, 2015